Interaksi Sosial Guru Dan Siswa Dalam Pembelajaran Sosiologi Di SMA - Chandra, Alex (Jurnal Pendidikan Sosiologi dan Humaniora, 2014)
The problem of this research is how social contact and social communication between teacher and students in learning sociology in class XI IPS of SMA Katolik Talino. The purpose of this research is to analyze how social contact and social communication between teacher and students in learning sociology. The using method is qualitative descriptive research with the object of the research is teacher and students in learning sociology. The result of this research is social interaction between teacher and students still not really good. This condition can be known by social contact and social communication between teacher and students that appears less closeness, less enthusiasm of studying, and there is no teacher’s apperception to students. From the finding can be concluded that social contact of the teacher and students in learning sociology in Class XI IPS of SMA Katolik Talino is not good and social communication between teacher and students is not good too.Keywords : The Social Interaction Of Teacher And Students, Sociology Learning